Carbon fiber manufacturing method

JP7636235B2Active Publication Date: 2025-02-26TEIJIN LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021057009
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-02-26
Estimated Expiration
2041-03-30

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、アクリロニトリル系炭素繊維前駆体繊維を用いた炭素繊維を製造する際に耐炎化および炭素化処理する工程での毛羽および単糸切れを抑制し、高強度かつ高品位な炭素繊維を安定的に得ることのできる、炭素繊維の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636235000001
    Figure 0007636235000001
Patent Text Reader

Abstract

To provide a manufacturing method of a carbon fiber capable of stably obtaining a high-strength and high-quality carbon fiber by suppressing fuzz and single yarn breakage in a step of flame-proofing and carbonization treatment during manufacture of the carbon fiber by using acrylonitrile-based carbon fiber precursor fiber.SOLUTION: There is provided a manufacturing method of a carbon fiber, the method includes a step of flame-proofing while applying a tension to a carbon fiber precursor fiber, in which a maximum value of a heat shrinkage stress at 50 to 200°C of the carbon fiber precursor fiber to be provided for flameproofing is 0.50 to 3.00 mN / dtex, a maximum value of a heat shrinkage stress at 200 to 300°C is 1.50 to 5.00 mN / dtex, and a tension applied to the carbon fiber precursor fiber during flameproofing is 1.00 to 5.00 mN / dtex.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing carbon fibers. [Background technology]

[0002] Carbon fiber has excellent specific strength and specific elasticity and is lightweight, so it is used as a reinforcing fiber for thermosetting and thermoplastic resins in a wide range of applications, including sports and general industrial applications, as well as aerospace and automotive applications.

[0003] In aerospace and automotive applications, there is a high demand for improved performance and productivity of carbon fiber composite materials. Because the properties of carbon fiber composite materials are derived from the properties of the carbon fiber itself, there is also a strong demand for improved strength of the carbon fiber.

[0004] Carbon fibers obtained using acrylonitrile-based fibers as precursor fibers have higher tensile strength than carbon fibers obtained using other fibers as precursor fibers, and are therefore used in carbon fiber composite materials that require particularly high performance.

[0005] In order to obtain high-performance, high-quality carbon fibers, it is important to suppress fuzzing and single-fiber breakage in the precursor fibers, acrylonitrile-based fibers, the flame-retardant fibers using these, and the pre-carbonized fibers using these, as well as in the carbon fibers, and for this reason it is important to improve the fiber convergence.

[0006] Japanese Patent Application Laid-Open No. 62-117818 discloses a method for obtaining carbon fibers with high tensile modulus and tensile strength that cannot be obtained by wet spinning, by flameproofing and carbonizing acrylonitrile precursor fibers obtained by dry and wet spinning under a constant tension. However, by simply treating the fibers at a constant tension in the flameproofing process, the strength and modulus are not sufficiently developed, and fiber breakage occurs frequently in the baking process, making it difficult to stably obtain high-quality carbon fibers.

[0007] JP 2004-300600 A proposes a method for obtaining carbon fibers with high strength and high elastic modulus by flame-retarding in a liquid phase. However, in this method, the treatment is performed in a liquid phase at high temperatures, and the solvent used acts as a plasticizer for the fibers, making it difficult to obtain flame-retarded fibers with high orientation. Even if an attempt is made to obtain carbon fibers with high strength and high elastic modulus, thread breakage frequently occurs in the baking process. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Laid-Open No. 62-117818 [Patent Document 2] JP 2004-300600 A Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention aims to provide a method for producing carbon fibers that can suppress fuzz and single-fiber breakage in the flame-retardant and carbonization treatment steps in producing carbon fibers using acrylonitrile-based carbon fiber precursor fibers, and can stably produce high-strength, high-quality carbon fibers. [Means for solving the problem]

[0010] The present invention relates to a method for producing a carbon fiber, which includes a step of flame-proofing a carbon fiber precursor fiber while applying tension to the carbon fiber precursor fiber, and a method for producing the same, comprising the steps of: the maximum value of the thermal shrinkage stress at 200 to 300°C is 0.50 to 3.00 mN / dtex, the maximum value of the thermal shrinkage stress at 200 to 300°C is 1.50 to 5.00 mN / dtex, and the tension applied to the carbon fiber precursor fiber during the flame retardation is 1.00 to 5.00 mN / dtex. Effect of the Invention

[0011] According to the present invention, it is possible to provide a method for producing carbon fibers that can suppress fuzz and single-fiber breakage during the flame-retardant and carbonization treatment steps in producing carbon fibers using acrylonitrile-based carbon fiber precursor fibers, and can stably produce high-strength, high-quality carbon fibers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below.

[0013] [Carbon fiber precursor fiber] The present invention is a method for producing carbon fibers, which includes a step of flame-proofing a carbon fiber precursor fiber while applying tension to the precursor fiber.

[0014] In the present invention, an acrylonitrile polymer is used as the carbon fiber precursor fiber to be subjected to flame retardation. As the acrylonitrile polymer, a polymer containing 90% by mass or more of an acrylonitrile component is preferably used. The acrylonitrile polymer may be a homopolymer containing 100% by mass of an acrylonitrile component, or a copolymer in which the acrylonitrile component is copolymerized with another monomer component. Examples of comonomers to be copolymerized with acrylonitrile include acrylic acid, itaconic acid and salts thereof, acrylic acid esters such as methyl acrylate and ethyl acrylate, and amides such as acrylamide.

[0015] The fineness of the carbon fiber precursor fiber is preferably 0.5 to 1.7 dtex. If it is less than 0.5 dtex, single yarn breakage is likely to occur due to contact with rollers or guides, and process stability is reduced, which is not preferable, while if it exceeds 1.7 dtex, a large structural difference occurs between the inner and outer layers during flame-proofing, which is not preferable because the strength and elastic modulus of the carbon fiber are reduced.

[0016] This carbon fiber precursor fiber has a maximum heat shrinkage stress of 0.50 to 3.00 mN / dtex at 50 to 200 ° C, and a maximum heat shrinkage stress of 1.50 to 5.00 mN / dtex at 200 to 300 ° C. If the maximum heat shrinkage stress at 50 to 200 ° C is less than 0.50 mN / dtex, high temperature or long-term heat treatment is required after drawing in the carbon fiber precursor manufacturing process, resulting in increased fuzz in the carbon fiber precursor. On the other hand, if it exceeds 3.00 mN / dtex, the tension at the beginning of the flame-proofing becomes too high, so that single yarn breakage and yarn breakage are likely to occur. If the maximum heat shrinkage stress at 200 to 300 ° C is less than 1.50 mN / dtex, the tension in the flame-proofing process is low and the orientation of the flame-proofed yarn is reduced, so that sufficient carbon fiber strength and elastic modulus cannot be obtained. On the other hand, if it exceeds 5.00 mN / dtex, the tension in the flame-resistant process becomes too high, causing single yarn breakage and yarn breakage, which leads to a decrease in the productivity and quality of the carbon fiber.

[0017] [Manufacturing method] The present invention is characterized in that a carbon fiber precursor fiber having the above-mentioned characteristics is used as the carbon fiber precursor fiber to be subjected to flame retardancy. This carbon fiber precursor fiber can be produced by further subjecting a drawn yarn that has been wet-drawn in a water bath by a conventional method in the production of carbon fiber precursor fiber, to steam drawing, and then to heat treatment.

[0018] The method for producing carbon fiber of the present invention includes the steps of preparing a spinning dope, spinning, wet drawing, applying an oil agent, steam drawing, heat treatment, flameproofing, and carbonization in this order. Each step will be described in detail below.

[0019] [Step of preparing spinning dope] The polymerization method of the polyacrylonitrile polymer can be any of known methods such as solution polymerization, suspension polymerization, and emulsion polymerization. As the polymerization catalyst used in the polymerization reaction, a known catalyst can be appropriately used depending on the polymerization method, and for example, a radical polymerization catalyst such as an azo compound or a peroxide, or a redox catalyst can be used. When a redox catalyst is used, examples of the reducing agent include sodium hydrogen sulfite, ammonium hydrogen sulfite, alkyl mercaptans, ascorbic acid, and the like. Examples of the oxidizing agent include potassium persulfate, sodium persulfate, ammonium persulfate, sodium chlorite, and hydrogen peroxide.

[0020] The precursor fiber bundle is preferably produced by spinning a spinning dope in which the polyacrylonitrile polymer is dissolved in a solvent. Examples of the solvent used in the spinning dope include aqueous solutions of inorganic compounds such as zinc chloride and sodium thiocyanate, and organic solvents such as dimethylacetamide, dimethylsulfoxide, and dimethylformamide. The solvent used in the spinning dope may be the same as or different from the solvent used in the polymerization step. When a polymerization method such as solution polymerization that can obtain a polymer solution in which a polymer is dissolved in a solvent is used in the polymerization step, the polymer solution may be used as the spinning dope without precipitating the polymer.

[0021] The polymer concentration of the spinning solution is preferably 3 to 40% by mass, more preferably 4 to 30% by mass, and particularly preferably 5 to 25% by mass, and the amount of the solvent is adjusted so that the concentration is within this range. By setting the polymer concentration within this range, a spinning dope can be obtained that is easy to spin and that is easy to obtain coagulated fibers with a dense interior. The higher the polymer concentration, the more the denseness of the interior of the coagulated fibers obtained in the spinning process is improved, making it easier to obtain precursor fibers that give high-strength carbon fibers. If the polymer concentration is too high, the viscosity of the spinning dope tends to increase and spinning stability tends to decrease.

[0022] [Spinning process] The spinning dope obtained above is spun through a spinneret and coagulated to obtain a coagulated fiber. The spinning can be performed by a known spinning method. From the viewpoint of the roundness and surface smoothness of the carbon fiber, it is preferable to adopt a dry-wet spinning method as the spinning method.

[0023] As the organic solvent constituting the aqueous organic solvent solution in the coagulation liquid used in the dry-wet spinning method, for example, an aqueous zinc chloride solution, dimethylacetamide, dimethylsulfoxide, or dimethylformamide can be used.

[0024] The spinneret for extruding the spinning dope is preferably equipped with 100 to 100,000, more preferably 1,000 to 80,000, and particularly preferably 3,000 to 50,000 discharge holes.

[0025] The hole diameter of the discharge hole of the spinneret is preferably 0.02 to 0.5 mm. When the hole diameter is 0.02 mm or more, the discharge linear velocity is suppressed, and stable discharge can be performed without the occurrence of pulsation, etc., so that an acrylonitrile fiber with excellent homogeneity can be obtained. And, when the hole diameter is 0.5 mm or less, the occurrence of fiber breakage during spinning is suppressed, and uniform discharge from each hole is possible due to sufficient pressure loss, so that spinning stability can be maintained.

[0026] [Wet stretching process] Next, the coagulated yarn obtained by the above method is washed with water and wet stretched to obtain a stretched yarn. This wet stretching is performed in a water washing bath, and the maximum temperature of the water washing bath is preferably 60 to 100° C., more preferably 70 to 100° C., and particularly preferably 80 to 100° C. If the temperature is less than 60° C., the stretchability decreases and a sufficient stretch ratio cannot be obtained, which is not preferable from the viewpoint of productivity because the speed of the carbon fiber precursor manufacturing process cannot be increased.

[0027] [Oil application step] An oil is applied to the obtained drawn yarn. The oil can be applied by immersing the drawn yarn in an aqueous solution containing the oil and bringing the surface of the drawn yarn into contact with the oil. From the viewpoints of adhesion between single fibers, heat resistance, releasability, and processability, a silicone-based oil is preferred.

[0028] As the silicone-based oil agent, amino-modified silicone, epoxy-modified silicone, and ether-modified silicone are preferably used. These may be used in combination of two or more kinds.

[0029] The amount of oil is preferably 0.01 to 10.0% by mass, more preferably 0.1 to 5.0% by mass, and particularly preferably 0.2 to 1.0% by mass. By setting the amount of oil in this range, it is possible to suppress the occurrence of thread breakage and fluff in the spinning process and the subsequent flame-resistant process, and to obtain high-quality carbon fiber precursor fibers and carbon fibers. If the amount of oil is less than 0.01% by mass, the oil is not sufficiently attached to the fiber surface, which is undesirable because it tends to increase the occurrence of thread breakage and fluff in the spinning process and the subsequent flame-resistant process. On the other hand, if the amount of oil exceeds 10.0% by mass, it is undesirable because it tends to cause problems such as the oil accumulating on the surfaces of fiber conveying rollers and guides in the spinning process and the flame-resistant process, causing the fibers to wrap around them and become a cause of thread breakage.

[0030] [Steam stretching process] The drawn yarn to which the oil agent has been applied is further subjected to steam drawing. Steam drawing is drawing performed in water vapor, and is also called steam drawing. The saturated steam pressure in the steam drawing is preferably 0.15 to 0.8 MPa, and the steam temperature is preferably 105 to 200°C, more preferably 110 to 180°C. If the saturated steam pressure is less than 0.15 MPa, the stretchability decreases and fluff and yarn breakage are likely to occur, which is not preferable. On the other hand, if it exceeds 0.8 MPa, the shaking of the fiber bundle due to the steam becomes large, which is not preferable. If the steam temperature is less than 105°C, the stretchability decreases and fluff and yarn breakage are likely to occur, which is not preferable. On the other hand, if it exceeds 200°C, it is not preferable in terms of process control and energy efficiency.

[0031] The steam drawing is preferably performed under a tension of 7.0 to 10.0 mN / dtex. If the tension is less than 7.0 mN / dtex, sufficient drawing is not possible, making it difficult to increase the strength of the carbon fiber, which is not preferred. On the other hand, if the tension exceeds 10.0 mN / dtex, the quality of the carbon fiber precursor fiber and the carbon fiber is reduced, which is not preferred.

[0032] In the steam drawing, the drawn yarn is drawn at a draw ratio of 1.5 to 10 times, preferably 1.8 to 5 times, and more preferably 2.0 to 3.0 times. A draw ratio of less than 1.5 times is not preferred because the productivity decreases, while a draw ratio of more than 10 times is not preferred because the quality of the carbon fiber precursor fiber and the carbon fiber decreases.

[0033] [Heat treatment process] The fiber after steam drawing is further heat-treated while relaxing. This heat treatment is performed at a draw ratio of 0.900 to 0.997 times and a temperature of 100 to 200 ° C. If the draw ratio is less than 0.900 times, the yarn sags, making it difficult to stably obtain a carbon fiber precursor. On the other hand, if it exceeds 0.997 times, the quality of the carbon fiber precursor fiber decreases and single yarn breakage occurs in the baking process because sufficient strain relaxation cannot be achieved, which is not preferable. If the heat treatment temperature is less than 100 ° C, single yarn breakage occurs in the baking process because strain relaxation cannot be achieved. On the other hand, if it exceeds 200 ° C, flame resistance progresses, and single yarn breakage or yarn breakage occurs during the manufacturing process of the carbon fiber precursor fiber. The heat treatment time is, for example, 1 to 120 seconds, preferably 2 to 60 seconds. If it is less than 1 second, the treatment time is too short and strain relaxation is difficult. On the other hand, if it exceeds 120 seconds, the equipment becomes large, leading to an increase in cost.

[0034] The total draw ratio through a series of wet drawing, steam drawing and heat treatment is preferably 10 to 20 times, more preferably 13 to 17 times. If it is less than 10 times, the speed cannot be increased sufficiently, which is undesirable as it reduces productivity. On the other hand, if it exceeds 20 times, it is undesirable as it is prone to single yarn breakage and yarn breakage during the manufacturing process of the carbon fiber precursor fiber.

[0035] By performing steam drawing and heat treatment in the above-mentioned manner, it is possible to obtain carbon fiber precursor fibers having a maximum heat shrinkage stress of 0.50 to 3.00 mN / dtex at 50 to 200°C and a maximum heat shrinkage stress of 1.50 to 5.00 mN / dtex at 200 to 300°C.

[0036] [Flame resistance process] Next, the carbon fiber precursor fiber obtained by the above method, which has a maximum heat shrinkage stress of 0.50 to 3.00 mN / dtex at 50 to 200°C and a maximum heat shrinkage stress of 1.50 to 5.00 mN / dtex at 200 to 300°C, is flame-retarded to obtain a flame-retarded fiber. The flame-retarding is performed at a temperature of 230 to 260°C for a treatment time of 30 to 120 minutes.

[0037] If the flame-stabilizing temperature is less than 230°C, the flame-stabilizing reaction of the acrylonitrile precursor fiber will not proceed, whereas if the temperature exceeds 260°C, the flame-stabilizing reaction will be so rapid that single yarn breakage or fiber bundle breakage will occur during the process.

[0038] If the flame-stabilizing time is less than 30 minutes, the flame-stabilizing reaction will be insufficient, causing a sudden weight loss and fiber bundle breakage in the subsequent carbonization process. On the other hand, if the time exceeds 120 minutes, the oil agent adhering to the acrylonitrile fiber surface will turn into tar, which is likely to cause sticking.

[0039] The carbon fiber precursor fiber to be subjected to the flame retardant treatment is particularly preferably a carbon fiber precursor fiber obtained by steam drawing under a tension of 7.0 to 10.0 mN / dtex and heat treatment at a draw ratio of 0.900 to 0.997 times and a temperature of 100 to 200°C.

[0040] In flame retardation, the tension applied to the carbon fiber precursor fiber is 1.00 to 5.00 mN / dtex. If the tension is less than 1.00 mN / dtex, the orientation of the carbon fiber does not improve, making it difficult to obtain high-strength carbon fiber. On the other hand, if the tension exceeds 5.00 mN / dtex, single yarn breakage and yarn breakage during flame retardation are more likely to occur, and the quality of the carbon fiber decreases.

[0041] [Carbonization process] Next, the flame-resistant fiber obtained by the above method is carbonized. Prior to this carbonization, it is preferable to perform pre-carbonization. This pre-carbonization is carried out in an inert atmosphere at a maximum temperature of 500 to 900°C, with a specific gravity of 1.5 to 1.7 g / cm 3 This is done by heat treating until

[0042] Following the preliminary carbonization, carbonization is carried out in an inert atmosphere at a maximum temperature of 1000 to 3000°C, preferably 1000 to 2000°C, and more preferably 1000 to 1800°C. In this carbonization, the nitrogen content in the carbon fiber bundle is reduced by keeping the maximum temperature at 1000°C or higher, and the strength of the carbon fiber is stably expressed. By keeping the maximum temperature at 3000°C or lower, a satisfactory carbonization yield can be obtained. EXAMPLES

[0043] The present invention will now be described in detail with reference to examples, which were evaluated by the following methods.

[0044] (1) Maximum shrinkage stress (maximum shrinkage stress at 50-200°C and 200-300°C) The precursor fiber was cut to 100 mm and separated to a mass of 3 mg. This was clamped in a measuring jig so that the test length was 10 mm. Thermomechanical measurements were performed using a TMA / SS-7100 (manufactured by Hitachi High-Tech Science Corporation). The fiber (sample) clamped in the measuring jig was placed in a furnace at a temperature of 20°C, and the temperature was raised to 400°C at a heating rate of 10°C / min while keeping the test length constant. At this time, the maximum stress values ​​that appeared at 50 to 200°C and the maximum stress values ​​that appeared at 200 to 300°C were measured.

[0045] (2) Strength The strand tensile strength of the carbon fiber bundle was determined according to the following procedure in accordance with the resin-impregnated strand test method of JIS-R-7608: 10 strands of the carbon fiber bundle were measured, and the average value was taken as the strand tensile strength.

[0046] (3) Elastic modulus The strand tensile modulus of the carbon fiber bundle was determined according to the following procedure in accordance with the resin-impregnated strand test method of JIS-R-7608: 10 strands of the carbon fiber bundle were measured, and the average value was taken as the strand modulus.

[0047] (4) Number of fluff The number of fluffs in the fiber bundle was evaluated by visually counting the number of fluffs observed in the fiber bundle when the carbon fiber bundle was run for 100 m at a speed of 1 m / min.

[0048] (5) Single yarn breakage A 1m fiber bundle was taken, and the number of broken single yarns was counted when the fiber bundle was spread out. Ten fiber bundles were measured, and the average value was taken as the number of broken single yarns.

[0049] Example 1 100 parts by mass of acetonitrile, 1 part by mass of itaconic acid, 0.003 parts by mass of octyl mercaptan as a chain transfer agent, and 360 parts by mass of dimethyl sulfoxide were mixed and placed in a reaction vessel equipped with a reflux tube and a stirring blade. After the space in the reaction vessel was replaced with nitrogen until the oxygen concentration reached 100 ppm, 0.003 parts by mass of 2,2'-azobis(isobutylnitrile (AIBN)) was added as a polymerization initiator, and a spinning dope with a concentration of 21% by mass was obtained by solution polymerization. The obtained spinning dope was discharged from a spinneret with a hole diameter of 150 μm and 3000 holes, and spun into the coagulation liquid with a distance of 10 mm between the spinneret and the coagulation liquid surface to obtain a coagulated thread. The coagulated thread was desolvated in a water washing tank and stretched 3.0 times (wet stretching), and immersed in a silicone-based oil bath to attach the oil. After that, it was dried by a heated roller and stretched (steam stretching) at a tension of 7.2 mN / dtex in water vapor at a pressure of 0.35 MPa. Then, it was heat-treated at 160°C with a heated roller at a stretch ratio of 0.990 to obtain an acrylonitrile-based carbon fiber precursor fiber bundle. When the heat shrinkage stress of the obtained acrylonitrile-based carbon fiber precursor fiber bundle was measured, the maximum value of the shrinkage stress at 50 to 200°C was 2.5 mN / dtex, and the maximum value of the shrinkage stress at 200 to 300°C was 2.0 mN / dtex.

[0050] This acrylonitrile-based carbon fiber precursor fiber was flame-retarded for 60 minutes at a temperature of 250°C and a tension of 3.00 mN / dtex, then pre-carbonized at a temperature of 580°C and a draw ratio of 1.10, and carbonized at a temperature of 1080°C and a draw ratio of 0.96 to obtain carbon fiber. The strength of the obtained carbon fiber was 5340 MPa and the elastic modulus was 245 GPa. No fluff or single yarn breakage of the carbon fiber was observed.

[0051] Example 2 Carbon fibers were obtained in the same manner as in Example 1, except that the draw ratio in the heat treatment after the steam drawing was 0.980 times. The strength of the obtained carbon fibers was 5440 MPa and the elastic modulus was 245 GPa. No fluff or single fiber breakage of the carbon fibers was observed.

[0052] Example 3 Carbon fibers were obtained in the same manner as in Example 1, except that the draw ratio in the heat treatment after the steam drawing was 0.997 times. The strength of the obtained carbon fibers was 5,300 MPa and the elastic modulus was 245 GPa. No fluff or single fiber breakage of the carbon fibers was observed.

[0053] Example 4 Acrylonitrile and itaconic acid were copolymerized by aqueous suspension polymerization in the presence of ammonium persulfate-ammonium hydrogensulfite and iron sulfate to obtain an acrylonitrile-based polymer consisting of acrylonitrile units / itaconic acid units=99 / 1 (mass ratio). This acrylonitrile-based polymer was dissolved in dimethyl sulfoxide to prepare a spinning dope with a concentration of 21% by mass.

[0054] Carbon fibers were obtained in the same manner as in Example 1, except that the tension of the steam drawing was 7.4 mN / dtex. The strength of the obtained carbon fibers was 5210 MPa and the elastic modulus was 245 GPa. The number of fluffs of the carbon fibers was 1 per 100 m, and no single fiber breakage was observed.

[0055] Comparative Example 1 Carbon fibers were obtained in the same manner as in Example 1, except that the draw ratio after steam drawing was 1.000 times and the temperature was room temperature. The strength of the obtained carbon fibers was 5,020 MPa and the elastic modulus was 245 GPa. The number of fluffs of the carbon fibers was 12 / 100 m, and the number of single fiber breaks was 2 / m.

[0056] Comparative Example 2 Carbon fibers were obtained in the same manner as in Example 1, except that the draw ratio after steam drawing was 1.000 times. The strength of the obtained carbon fibers was 5120 MPa, and the elastic modulus was 245 GPa. The number of fluffs of the carbon fibers was 3 / 100 m, and the number of single fiber breaks was 1 / m.

[0057] Comparative Example 3 Carbon fibers were obtained in the same manner as in Example 1, except that the draw ratio after steam drawing was 1.000 times and the temperature was 180° C. The strength of the obtained carbon fibers was 5080 MPa and the elastic modulus was 245 GPa. The number of fluffs of the carbon fibers was 5 pieces / 100 m, and the number of single fiber breaks was 1 piece / m.

[0058] Comparative Example 4 Carbon fibers were obtained in the same manner as in Example 4, except that the draw ratio after steam drawing was 1.000 times and the temperature was room temperature. The strength of the obtained carbon fibers was 4980 MPa and the elastic modulus was 245 GPa. The number of fluffs of the carbon fibers was 15 / 100 m, and the number of single fiber breaks was 2 / m.

[0059] Comparative Example 5 Acrylonitrile, methyl acrylate, and itaconic acid are copolymerized by aqueous suspension polymerization in the presence of ammonium persulfate, ammonium hydrogen sulfite, and iron sulfate to obtain acrylonitrile. An acrylonitrile-based polymer having a mass ratio of methyl acrylate / itaconic acid unit=95 / 4 / 1 was obtained. This acrylonitrile-based polymer was dissolved in dimethyl sulfoxide to prepare a spinning dope having a concentration of 21 mass %.

[0060] Carbon fibers were obtained in the same manner as in Example 4, except that the composition was changed and the draw ratio after steam drawing was set to 1.000 times. The strength of the obtained carbon fibers was 4900 MPa and the elastic modulus was 245 GPa. The number of fluffs of the carbon fibers was 45 pieces / 100 m, and the number of single fiber breaks was 8 pieces / m.

[0061] Comparative Example 6 Acrylonitrile, methyl acrylate, and itaconic acid were copolymerized by aqueous suspension polymerization in the presence of ammonium persulfate-ammonium hydrogen sulfite and iron sulfate to obtain an acrylonitrile-based polymer consisting of acrylonitrile units / methyl acrylate / itaconic acid units=95 / 4 / 1 (mass ratio). This acrylonitrile-based polymer was dissolved in dimethyl sulfoxide to prepare a spinning dope with a concentration of 21% by mass.

[0062] Carbon fibers were obtained in the same manner as in Example 4, except that the composition was changed and the draw ratio after steam drawing was set to 0.997 times. The strength of the obtained carbon fibers was 4920 MPa and the elastic modulus was 245 GPa. The number of fluffs of the carbon fibers was 32 / 100 m, and the number of single fiber breaks was 5 / m.

[0063] [Table 1] [Industrial Applicability]

[0064] The carbon fiber produced by the carbon fiber production method of the present invention can be used as a raw material for carbon fiber composite materials for sports and general industrial applications, aerospace applications, automotive applications, and the like.

Claims

[Claim 1] A method for producing carbon fibers, comprising a step of flame-proofing a carbon fiber precursor fiber while applying tension thereto, characterized in that the carbon fiber precursor fiber to be flame-proofed has a maximum heat shrinkage stress of 0.50 to 3.00 mN / dtex at 50 to 200°C and a maximum heat shrinkage stress of 1.50 to 5.00 mN / dtex at 200 to 300°C, a tension applied to the carbon fiber precursor fiber during flame-proofing is 1.00 to 5.00 mN / dtex, the carbon fiber precursor fiber to be flame-proofed is a carbon fiber precursor fiber produced by steam drawing and a heat treatment thereafter, the steam drawing is performed under a tension of 7.0 to 10.0 mN / dtex, and the heat treatment is performed at a draw ratio of 0.900 to 0.997 at a temperature of 100 to 200°C.

Citation Information

Patent Citations

  • Piperidine derivatives and preparation method

    JP1977042885A

  • Lead storage battery with eletrolyte circulating device

    JP1985039763A

  • High-strength and high-modulus carbon fiber and production thereof

    JP1987117818A

  • Precursor for high-strength carbon fiber and production thereof

    JP1988159526A

  • Flame-resistant fiber, carbon fiber and method for producing these fibers

    JP2004300600A